PENERAPAN MATEMATIKA PADA ILMU EKONOMI FUNGSI KONSUMSI DAN TABUNGAN - Dewi, Ellysa Fitia; Suwito, Dewi Kartika; Aminnurlah, Muhammad Fachrul; Suci, Nayla Amalia; Ramadhani, Putri Hayuki; Pujiwardhani, Salsa Nabila; Faizin, Wahyu Tegar (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The application of mathematics in economics provides an important analytical framework for understanding the relationship between consumption, savings, and income. This article discusses consumption and savings functions based on classical economic theories such as The General Theory of Employment, Interest, and Money by J.M. Keynes as well as the permanent income theory by Milton Friedman. The consumption function is formulated as C=a+bY, where consumption is affected by national income and initial consumption. Meanwhile, the savings function is formulated as S=-a+(1-b)Y, which shows the remaining income after consumption. This research uses a descriptive approach and literature review by utilizing quantitative and qualitative data. The analysis shows that consumption and savings are closely related to household income. In addition, this article also explains the concept of market equilibrium, which is achieved when demand equals supply (Qd=Qs). The findings confirm that the application of mathematics can help analyze and solve various economic problems effectively and measurably.